NOVEL DRUG TARGETS TO AUGMENT TEMOZOLOMIDE SENSITIVITY IN HIGH-GRADE BRAIN TUMOURS. (3rd October 2018) - Carmell, Natasha; Brown, Stephen; Khamisy, Sherif; Collis, Spencer
Abstract: Brain tumours kill more children and adults under 40 than any other cancer. Approximately half of primary brain tumours are high-grade malignancies known as glioblastoma multiforme (GBM). Current treatment regimes for GBM combine de-bulking surgery with radiotherapy and the chemotherapeutic DNA alkylating agent temozolomide (TMZ). However, the mean survival for GBM patients is 15 months, with less than 10% of GBM patients surviving 5 years. This devastating prognosis highlights the urgent need for the development of novel agents to improve GBM treatment. A kinome-wide RNAi screen was carried out in a TMZ resistant GBM cell line. Cells were incubated with a low dose of TMZ and a non-toxic kinase-targeting RNAi. Cell viability was calculated by high-content microscopy and algorithm-based scoring of Hoechst-positive cells. Target validation studies of hits were carried out using additional RNAi libraries and small-molecule compound dose-escalation studies in additional GBM cell lines. We identify Extracellular Regulated Kinase 5 (ERK5) as a novel drug target to augment TMZ sensitivity. ERK5 is part of the MAPK signalling cascade, involved in cell survival and proliferation pathways, as well as cell differentiation and motility. ERK5 is dysregulated in many cancers and over-expression often results in a worse prognosis. At the mRNA level, ERK5 expression in GBM has been shown to be upregulated compared to normal tissue (REMBRANT Database). Using a range of siRNA and small molecule inhibitors in a panel of GBM cells, we have shown ERK5 inhibition sensitises GBM cell lines to TMZ. This will finding will be validated further using primary patient derived cultures and may potentially provide a novel target to improve GBM patient prognosis.